The Emerging Role of FOXL2 in Regulating the Transcriptional Activation Function of Estrogen Receptor β: An Insight Into Ovarian Folliculogenesis. (January 2017) - Hirano, Mana; Wada-Hiraike, Osamu; Fu, Houju; Akino, Nana; Isono, Wataru; Sakurabashi, Ayako; Fukuda, Tomohiko; Morita, Yoshihiro; Tanikawa, Michihiro; Miyamoto, Yuichiro; Nishi, Yoshihiro; Yanase, Toshihiko; et al.
Germline mutations of the fork-head transcriptional factor forkhead box L2 (FOXL2) predispose embryos to autosomal-dominant blepharophimosis–ptosis–epicanthus inversus syndrome with primary ovarian insufficiency in female patients, but the mechanisms of FOXL2 in ovarian follicular development remain elusive. Estrogens produced by ovarian granulosa cells and estrogen receptor (ER) α and ERβ play fundamental roles in ovarian pathophysiology, and a previous study revealed that ERα and ERβ physically interact with FOXL2. However, the underlying functions of these interactions have not been investigated. Herein, we report an ERβ-specific repressive function of FOXL2. Histological examination demonstrated that FOXL2 expression tends to be intense during early follicular development. Immunoprecipitation revealed that ERβ and FOXL2 interact in a ligand-independent manner. In vitro pull-down assays revealed a direct interaction between FOXL2 and the activation function (AF)-1/2 domain of ERβ. The expression of FOXL2 represses the ligand-dependent transcriptional activation of ERβ, but FOXL2 does not influence the ligand-dependent transcriptional activation of ERα. Consistent with these results, RNA interference-mediated depletion of FOXL2 stimulates the expression of the ERβ-downstream gene p450 aromatase. The convergence between FOXL2 functions and ERβ-mediated transcription in the ovary suggests the putative mechanism of FOXL2 in early-phase follicular development, which may be partially attributed to the regulation of ERβ-dependent gene expression.